Critical Discourse Analysis on Representation of Racism and Solidarity in Adidas's Tweets - Desi Indrawati (Bina Nusantara University, 2021)
The research aimed to analyze how Adidas uses Twitter to convey messages about racism and solidarity in its tweets. Methodologically, the research applied a descriptive qualitative study on the representation of racism in Adidas’s tweets involving (1) What are the themes of discourses that represent racism and solidarity in Adidas’s tweets? (2) What is the representation of racism and solidarity in Adidas’s tweets? and (3) What are the meanings of Adidas’s tweets? Twelve tweets from Adidas were collected, coded, analyzed, and described using Critical Discourse Analysis (CDA). It was an effective method for deconstructing the identity of Twitter users to make arguments on the themes exposed during coding. The research findings reveal that the declarative statement and humanitarian as the most themes in Adidas’s tweets are the ones that give straightforward and positive messages to Twitter users and followers. The findings also indicate firm and meaningful tweets for Adidas to speak out against racism and spread solidarity through Twitter. However, those tweets also give the messages about their commitment to always supporting the black community, their black employees, the Asian community, and the Black Lives Matter event to embody valuable and eternal change through solidarity, unity, and commitment against racism.